DESIGNING RECOMMENDATIONS BASED ON VISITOR SATISFACTION USING CORRELATION, REGRESSION AND IMPORTANCE-PERFORMANCE ANALYSIS AT TANJUNG PIAI NATIONAL PARK - Muhammad Mada Novarianto; Singgih Saptadi (Program Studi Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2026)
Tanjung Piai National Park is a park located at the southernmost point of mainland Asia in Johor, Malaysia. It possesses significant ecological and cultural value through its unique mangrove ecosystems, biodiversity, and geographical landmark status; however, despite these assets, the park has struggled with persistently stagnant visitor numbers, a narrow demographic base, and deteriorating physical infrastructure, all of which threaten its long-term viability as both a conservation site and an ecotourism destination. Previous studies have primarily focused on ecological and community-based aspects of the park. This study aims to measure visitor satisfaction across five ecotourism dimensions, based on a previous study by Anh Toai Le which are Destination Attraction, Ecotourism Services, Staff Quality, Price Fairness, and Infrastructure in order to measure and evaluate how each dimension influences visitors' willingness-to-visit, and produce a prioritized, data-driven set of management recommendations. A quantitative survey-based methodology was employed, distributing Likert-scale structured questionnaires both online and on-site to a total of 527 unique respondents, with data analyzed through Pearson correlation analysis, multiple linear regression, and Importance–Performance Analysis (IPA). The results revealed that Destination Attraction (β = 0.398) and Infrastructure (β = 0.339) are the strongest predictors of willingness-tovisit, collectively with all five dimensions explaining approximately 59.2% of the variance in revisit intention (R² = 0.592); the IPA matrix further identified Ecotourism Services as the sole dimension in the